Implementation of Electronic-Based Decision Making in Sports Event Management of Bone Regency Youth and Sports Department - M. Awaluddin; Hezron Alhim Dos Santos; Sugirah Nour Rahman; Maria Herlinda Dos Santos; Hasnah Hasnah (Journal La Bisecoman, 2024)
The implementation of Electronic-Based Decision Making (EBDM) in regarding to the management of the sports events particularly at Bone Regency Youth and Sports Department, can be seen as a breakthrough. In this paper, an evaluation of the various aspects under EBDM is undertaken from the perspective of the efficiency, accuracy and the degree of stakeholder engagement in the decision-making process. In this work, which uses interviews, observations, and document analysis, the empirical evidence of how EBDM has reduced decision time and increased the precision of decisions while eliminating traditional ‘time-consuming and error-prone’ methods is presented. Nevertheless, it has not been without problems some of which are staff resistance to new technologies and data safety issues. Some of the crucial recommendations that have been found in the study incldue the need for constant training, enhanced data handling, and successful implementation of stakeholder engagement in the case of EBDM. Despite these benefits of EBDM in enhancing the quality of decision made, the study sad that there exists the need to continue assessing various decisions to ensure they retain their quality and meet emerging risks. According to the research, EBDM, when implemented, has the potential to significantly enhance operational effectiveness but only when implemented in a way that adequately takes into consideration the need to address associated technological as well as workforce issues for the program to work in the long run.